ANALISA PENGARUH SELF IMAGE CONGRUITY, RETAIL SERVICE QUALITY, DAN CUSTOMER PERCEIVED SERVICE QUALITY TERHADAP REPURCHASE INTENTION DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING DI BROADWAY BARBERSHOP SURABAYA - Livia Margarita Widjiono; Edwin Japarianto (Institute of Research and Community Outreach - Petra Christian University, 2015)
This study aims to analyze the influence of Self Image Congruity, Retail Service Quality, and Customer Perceived Service Quality on Repurchase Intention with Customer Satisfaction as intervening variable. This study uses 100 respondents and path analysis method. The research result obtained, there is no significant effect of Self Image Congruity on Customer Satisfaction, there is a significant effect of Retail Service Quality on Customer Satisfaction, there is no significant effect of Customer Perceived Service Quality on Customer Satisfaction, there is a significant effect of Customer Satisfaction on Repurchase Intention, there is a significant effect of Self Image Congruity on Repurchase Intention, there is a significant effect of Customer Perceived Service Quality on Repurchase Intention.